Computed tomography severity index and serum CRP concentration for predicting the severity of acute pancreatitis - Nagarchi, Abdul Rashid; Babu, Manohar; Saad, Syed (International Surgery Journal, 2021)
Background: The assessment of the severity of pancreatitis is important for management of this challenging disease. An accurate system which could predict the severity and identify the local extent and complications of a serious inflammation is beneficial for the patient outcome. The aim was to establish the value of the CTSI in predicting the severity of acute pancreatitis and to compare it with the accuracy of the serum CRP concentrations. Methods: Prospective clinical study based on analysis of 55 patients. Each patient underwent thorough clinical and biochemical analysis and CECT abdomen. CTSI within 5 days, serum CRP level 48 hours after admission. Results: The mean values of predictive markers in the mild and the severe pancreatitis groups were: computed tomography severity index 1.26 and 6.30 (p<0.001) and CRP 96.0 mg/l and 192.4 mg/l (p<0.001), respectively. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated for the CTSI (greater than 3: 85%, 98%, 92%, 95%, and 95%) and for CRP (equal to, or greater than 150 mg/l: 85%, 74%, 50%, 94%, and 76%). Conclusions: We found a close correlation with CRP levels and the CTSI of patients having severe pancreatitis and a CTSI score greater than 3 had a serum CRP level in excess of 150 mg/l. CRP is incapable of identifying local complications. The CTSI is a reliable method for staging the severity of acute pancreatitis and showing the local extent of the inflammation and the occurrence of local complications.